2019
DOI: 10.7150/jca.32065
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TUG1 mediates 5-fluorouracil resistance by acting as a ceRNA of miR-197-3p in colorectal cancer

Abstract: One major reason for the failure of advanced colorectal cancer (CRC) treatment is the occurrence of chemoresistance to fluoropyrimidine (Fu)-based chemotherapy. Accumulating evidence indicates that long non-coding RNAs (lncRNAs) play a critical role in cancerous processes as either oncogenes or tumor suppressor genes. Here, we observed lncRNA TUG1 was associated to the 5-Fu resistance in colorectal cancer. Firstly, quantitative analysis indicated that TUG1 was significantly increased in recurrence CRC patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…There is increasing evidence that a high lncRNA expression is significantly correlated with unfavorable CRC prognosis. The elevated expressions of lncRNA TTN-AS1, XIST, TUG1, and SNHG12 indicate poor prognoses for CRC patients (Liu et al, 2018;Liu Y. et al, 2019;Wang M. et al, 2019;. Our multivariate survival study proved that LINC00115 is an independent prognostic factor for relapse and poor survival in CRC patients.…”
Section: Discussionmentioning
confidence: 54%
“…There is increasing evidence that a high lncRNA expression is significantly correlated with unfavorable CRC prognosis. The elevated expressions of lncRNA TTN-AS1, XIST, TUG1, and SNHG12 indicate poor prognoses for CRC patients (Liu et al, 2018;Liu Y. et al, 2019;Wang M. et al, 2019;. Our multivariate survival study proved that LINC00115 is an independent prognostic factor for relapse and poor survival in CRC patients.…”
Section: Discussionmentioning
confidence: 54%
“…15 However, nearly 50% of colorectal cancer patients showed no response to 5-Fu, and more and more studies reported that fluorouracil resistance led to failure of CRC treatment. [16][17][18] But the mechanism is not clear. Therefore, biomarkers predicting the efficacy of fluorouracil are urgently needed in CRC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that a high lncRNA expression is signi cantly correlated with unfavorable CRC prognosis. The elevated expressions of lncRNA TTN-AS1, XIST, TUG1 and SNHG12 indicate poorer prognoses of CRC patients [17,[22][23][24]. Our multivariate survival study proved that LINC00115 are independent prognostic factors for poor relapse-survival in CRC patients.…”
Section: Discussionmentioning
confidence: 54%